Interoceptive accuracy correlates with precision of time perception in the millisecond range - Uraguchi, Maki; Maulina, Venie Viktoria Rondang; Ohira, Hideki (Frontiers in Neuroscience, 2022)
It has been proposed that accuracy in time perception is related to interoceptive accuracy and vagal activity. However, studies investigating time perception in the supra-second range have provided mixed results, and few studies have investigated the sub-second range. Moreover, there is a lack of studies investigating the relationship between precision in time perception and interoceptive accuracy. A recent meta-analytic review of neuroimaging studies proposed a dynamic interaction between two types of timing processing—an endogenous time keeping mechanism and the use of exogenous temporal cues. Interoceptive accuracy may affect both accuracy and precision of primary temporal representations, as they are generated based on the endogenous time keeping mechanism. Temporal accuracy may vary when adapted to the environmental context. In contrast, temporal precision contains some constant noise, which may maintain the relationship with interoceptive accuracy. Based on these assumptions, we hypothesized that interoceptive accuracy would be associated with temporal precision in the sub-second range, while vagal activity would be associated with temporal accuracy. We used the temporal generalization task, which allowed us to calculate the indices of temporal accuracy and temporal precision in line with the existing research, and also compute the index of participants’ sensitivity according to the signal detection theory. Specifically, we investigated whether 1) interoceptive accuracy would correlate with temporal accuracy, temporal precision, or sensitivity and 2) resting-state vagal activity would correlate with temporal accuracy, temporal precision, or sensitivity. The results indicated that interoceptive accuracy was positively correlated with temporal precision as well as sensitivity, but not with temporal accuracy, in the sub-second range time perception. Vagal activity was negatively correlated only with sensitivity. Furthermore, we found a moderation effect of sensitivity on the relationship between vagal activity and perceived duration, which affected the association between vagal activity and temporal accuracy. These findings suggest the importance of precision as an aspect of time perception, which future studies should further explore in relation to interoception and vagal activity, and of the moderation effects of factors such as participants’ sensitivity in this context.